Is peritoneoscopic-assisted Tenckhoff Catheter Insertion safe and effective in our nephrologists' hand? - Ahmad, MK; Seman, Mohd Ramli; Draman, Che Rosle; Wan Ali, Wan Ahmad Syahril Rozli; Ramli, Norazsida (2013)
Background: The practice of peritoneal dialysis (PD) catheter insertion by nephrologists has been advo¬cated to enhance PD penetration with encouraging outcome as shown in several centres. In this study, we evaluate the safety and effectiveness of our catheter insertion via peritoneoscopic method.